1977
DOI: 10.1084/jem.145.6.1559
|View full text |Cite
|
Sign up to set email alerts
|

Presence on idiotype-specific suppressor T cells of receptors that interact with molecules bearing the idiotype.

Abstract: All A/J mice produce anti-p-azophenylarsonate (anti-Ar) antibodies, some of which share a cross-reactive idiotype. The idiotype can be suppressed by treatment with anti-idiotypic antiserum before immunization, although normal concentrations of anti-Ar antibodies are synthesized. We have previously reported that such suppressed mice, if hyperimmunized and then allowed to rest, contain up to 10% of splenic T cells which form rosettes with autologous RBC coated with Fab fragments of anti-Ar antibodies bearing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

1978
1978
1998
1998

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 125 publications
(59 citation statements)
references
References 15 publications
7
51
1
Order By: Relevance
“…Studies from other laboratories have also demonstrated anti-idiotypic T cells involved in helper (21,22,(25)(26)(27) and suppressor (28)(29)(30)(31)(32)(33) cell activity. It might be envisioned that the anti-idiotypic T cell population could be divided into two distinct groups based on differences in the immunization procedures used to induce these cells and ultimately on differences in the specificity of the T ceils.…”
Section: Discussionmentioning
confidence: 99%
“…Studies from other laboratories have also demonstrated anti-idiotypic T cells involved in helper (21,22,(25)(26)(27) and suppressor (28)(29)(30)(31)(32)(33) cell activity. It might be envisioned that the anti-idiotypic T cell population could be divided into two distinct groups based on differences in the immunization procedures used to induce these cells and ultimately on differences in the specificity of the T ceils.…”
Section: Discussionmentioning
confidence: 99%
“…In most studies of idiotype-specific suppression of a B cell response, suppressor cells have been induced by administration of anti-idiotypic antiserum (7,10,19), idiotype alone (4,20), or idiotype conjugated to syngeneic cells (9). The operation of such an idiotypic suppressor mechanism during the normal course of a humoral immune response would be more directly demonstrated if antigen-induced suppressor cells, acting in an idiotype-specific manner, could be elicited by antigen.…”
mentioning
confidence: 99%
“…In experiments in animals on the regulatory action of antiidiotypic antibodies, idiotypic suppression can result from direct interaction of the antiidiotypic antibodies with the receptor of the antibody-forming B cell, as well as from induction of idiotype-specific suppressor T cells (5,7,9,21). Idiotype-positive peripheral blood B cells may be precursors of the plasma cells that are localized in joint tissue and are producing RF (22,23).…”
Section: Discussionmentioning
confidence: 99%